Penerapan Manajemen Kurikulum Merdeka Belajar dalam Meningkatkan Mutu Pembelajaran di SMP Negeri 1 Pamatang Silimahuta - Saragih, Afny Eldesty; Saragih, Hisarma; Nainggolan, Pinondang; Damanik, Sarintan E.; Saragih, Ramainim (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to evaluate the planning, implementation, and constraints of the independent curriculum management at SMP Negeri 1 Pamatang Silimahuta. It uses a qualitative research method. Data was collected through observation, interviews, and documentation involving subjects such as the principal, vice principal for curriculum, teachers, students, and parents. The data analysis techniques used include data reduction, data presentation, data validity, credibility, and drawing conclusions and verification. The results of the study showed that the planning and implementation of the Independent Learning Curriculum at SMP Negeri 1 Pamatang Silimahuta were carried out inclusively by involving all stakeholders, including parents of students, in supporting project-based learning and strengthening character education. Despite facing challenges such as lack of teacher readiness and limited facilities and infrastructure, the implementation of this curriculum showed positive results, marked by increased student enthusiasm and commitment from stakeholders. Evaluation was carried out through observation of changes in student attitudes and learning outcomes, with the hope that this curriculum will continue to be developed as an educational solution that is relevant to the demands of the times